Sustainable Solutions to Poverty: Is BLT Truly a Pro-poor Policy? - Putri, Amelia; Bessie, Loudewyk; Anabelle, Jovita; Herwanto, Trisno (KnE Social Sciences, 2025)
Structural poverty has been an ongoing issue that plagues Indonesia. The situation worsened during the COVID-19 era, revealing the social inequity between lower-class and higher-class citizens, and creating an urgency for the Indonesian government to implement a policy approach oriented towards the needs of the impoverished community (pro-poor policy). A government aid program was created to tackle this issue in the form of an unconditional cash program called Direct Cash Transfers (BLT). However, the sustainability of this program as a long-term solution was put into question. This study aims to solve whether BLT is truly a sustainable pro-poor approach to poverty. Various literature reviews would be used to formulate a conceptual framework to define pro-poor policies. Based on secondary data analysis, BLT is found to lean towards a viral-based policy rather than a pro-poor policy. The success of BLT implementation is often misused and weaponized for politicians’ private agendas and fails to create lasting effects and independence within the lower-class communities, trapping vulnerable people in the poverty cycle. The inability of the BLT program to provide access to various assets for its citizens and its hasty creation cemented the conclusion that BLT is not a pro-poor policy.